Managerial coaches’ enacted behaviors and the beliefs that guide them: perspectives from managers and their coachees - Adele, Beth; Ellinger, Andrea D. (Frontiers in Psychology, 2024)
Managerial coaching is considered a powerful developmental intervention in the workplace that has gained tremendous popularity in recent years. A growing base of scholarship examining the efficacy of this form of coaching has identified numerous benefits, primarily for employees receiving this form of coaching, and some limited attention has focused on benefits for managers who coach. However, an important topic related to managerial coaching that has gone under-explored is the beliefs that managers have about coaching. Since beliefs often guide behaviors, obtaining a more robust understanding of the beliefs that guide managers who serve as coaches is warranted and several scholars have called for more research on this aspect of managerial coaching (Carvalho et al., 2022; Ellinger et al., 2018). Therefore, the study reported here presents a subset of findings that relate to the coaching behaviors that managers enact along with a comprehensive understanding of their guiding beliefs. These specific findings are drawn from a larger qualitative multi-case study employing an adaptation of the critical incident technique that was designed to examine the beliefs, behaviors, and learning and development outcomes for both managers who coach and their respective coachees. This larger study obtained perspectives about these aspects of managerial coaching from both the coaches and coachees which also reflects an approach seldom taken when researching managerial coaching. Four research questions are addressed here: 1) What are the behaviors enacted by managers who coach (facilitate the learning of) their employees from the perspective of managers; 2), what are the behaviors enacted by managers who coach (facilitate the learning of) their employees from the perspective of employees; 3) What are the beliefs held by managers who coach (facilitate the learning of) their employees from the perspective of managers; and, 4) What are the beliefs held by managers who coach (facilitate the learning of) their employees from the perspective of their employees (coachees)? In addition to thick rich descriptions that illustrate these findings, implications for theory, research, and practice are also discussed.